Exploration of neuroprotective strategies in patients with acute promyelocytic leukemia complicated by cerebral hemorrhage - Jing Hu; Wentao Lai (Frontiers in Medicine)
Acute promyelocytic leukemia (APL) is a highly lethal hematological malignancy associated with various complications, among which cerebral hemorrhage is one of the most severe. Implementing effective neuroprotective strategies for APL patients experiencing cerebral hemorrhage is crucial. This article aims to explore the application of neuroprotective strategies in these patients, analyzing their mechanisms, clinical efficacy, and future research directions. By reviewing existing literature, we reveal the potential of neuroprotective strategies to improve prognosis, reduce neurological damage, and promote recovery, thereby providing guidance for clinical practice.